La minga as social imagery, A regard to the indian resilience pedagogy in Colombia (2020)
The current work aims at addressing one of the social manifestations in the culture of indigenous resistance in Colombia, such as the Minga. The proposal is original meanwhile an ancestral practice is recovered for the history of education. The minga as an expresión of a collective pedagogical practice is a part of the teachings of a large part of the Andean indigenous peoples of Colombia, and that merge to build, prepare or cultivate land or collect crops, and in our case, we want to present the demonstration as a form of social resistance, of their democratic rights and actions against the Peace Agreement. Methodologically, it is a desk-based research that is epistemologically focused on the epistemologies of the south and the tradition of the French Annalist School, British Marxist historians and Alternative Pedagogies (Mora-García, 2019). From which it is concluded that the recovery of ancestral imaginaries through La Minga allows us to promote the Pedagogy of Resilience for Peace.